L’expérience du quotidien dans Buffy the Vampire Slayer - Hélène Monnet-Cantagrel (Mise au Point)
Everyday life is a notion often considered to be vague. Nevertheless social sciences and humanities conceptualize it in a way which enables it to grasp its different levels and from which the relationship to everyday life in audiovisual fiction can be examined. This is what this article aims to demonstrate by using the example of Buffy the Vampire Slayer, the movie and the series. The goal is to examine the processes involved and how these contribute to creating an everyday effect.